Two solution representations for solving multi-depot vehicle routing problem with multiple pickup and delivery requests via PSO. (November 2015) - Kachitvichyanukul, Voratas; Sombuntham, Pandhapon; Kunnapapdeelert, Siwaporn
Highlights: Extends a previously published PSO algorithm for solving the GVRP-MDPDR. Two new solution representations, SD2 and SD3 for PSO algorithm are developed. The algorithms are tested with benchmark problem instances for GVRP-MDPDR. The results show that both SD2 and SD3 can provide better quality solutions. SD3 is superior to SD2 in terms of quality of solution in most test cases. Abstract: Two solution representations for solving the generalized multi-depot vehicle routing problem with multiple pickup and delivery requests (GVRP-MDMPDR) is presented in this paper. The representations are used in conjunction with GLNPSO, a variant of PSO with multiple social learning terms. The computational experiments are carried out using benchmark test instances for pickup and delivery problem with time windows (PDPTW) and the generalized vehicle routing problem for multi-depot with multiple pickup and delivery requests (GVRP-MDMPDR). The preliminary results illustrate that the proposed method is capable of providing good solutions for most of the test problems.